New synonyms and typifications in Psidium species (Myrtaceae) described by João Rodrigues Mattos and the importance of maintaining scientific collections - Tuler, Amélia Carlos; Carrijo, Tatiana Tavares; Peixoto, Ariane Luna (Phytotaxa, 2019)
With approximately 100 species, Psidium Linnaeus (1753: 470) is one of the largest genera of the family Myrtaceae. The genus has a Neotropical distribution (Landrum & Kawasaki 1997, WCSP 2018), with Brazil being regarded as its center of diversity and endemism in eastern South America with 60 documented species (Flora do Brasil 2020 under construction, 2018).